2014
DOI: 10.1021/es504420n
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Soil Legacy Phosphorus Transformation in Long-Term Agricultural Fields Using Sequential Fractionation, P K-edge XANES and Solution P NMR Spectroscopy

Abstract: Understanding legacy phosphorus (P) build-up and draw-down from long-term fertilization is essential for effective P management. Using replicated plots from Saskatchewan, Canada, with P fertilization from 1967 to 1995 followed by either P fertilization or P cessation (1995-2010), soil P was characterized in surface and subsurface layers using sequential fractionation, P K-edge X-ray absorption near-edge structure (XANES) and solution (31)P nuclear magnetic resonance (P NMR) spectroscopy. Legacy P from a 28-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
118
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(123 citation statements)
references
References 59 publications
5
118
0
Order By: Relevance
“…Generally, the P components were analyzed by solution 31 P NMR including phosphonates, orthophosphate, orthophosphate monoesters, orthophosphate diesters, pyrophosphate and polyphosphate, and the orthophosphate monoesters include some of components, such as phytate, Glucose-6-phosphate (Cade-Menun, 2005;CadeMenun and Preston, 1996;Turner et al, 2005). This method has been successfully applied for analyzed the soil, sediment (river, lake and marine) and manure (Vincent et al, 2013;Liu et al, 2015;McDowell et al, 2006;Cade-Menun et al, 2002;Ding et al, 2013;Zhang et al, 2016;Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the P components were analyzed by solution 31 P NMR including phosphonates, orthophosphate, orthophosphate monoesters, orthophosphate diesters, pyrophosphate and polyphosphate, and the orthophosphate monoesters include some of components, such as phytate, Glucose-6-phosphate (Cade-Menun, 2005;CadeMenun and Preston, 1996;Turner et al, 2005). This method has been successfully applied for analyzed the soil, sediment (river, lake and marine) and manure (Vincent et al, 2013;Liu et al, 2015;McDowell et al, 2006;Cade-Menun et al, 2002;Ding et al, 2013;Zhang et al, 2016;Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Three of these studies identified only broad compound classes [10,58,59], one identified the majority of peaks [60] and three identified peaks in detail [61][62][63]. In North America, there was one study from Mexico [22], five from Canada [23,32,33,64,65] and five from the USA [31,[66][67][68][69]. The early studies identified only broad peaks [22,23,64,66].…”
Section: P-nmr Studies Of Cropland Soilsmentioning
confidence: 99%
“…Of the 44 studies listed in Table 1, many do not even include measures of soil test P (STP), and only nine include information on yield or P balances [48, 54, 55, 59-61, 65, 70, 75]. Of these nine, only six identified peaks in enough detail (M or D) to identify trends in P forms other than orthophosphate [48,54,60,61,65,75]. I will focus on these studies in more detail, and they are summarized in Table 2.…”
Section: P-nmr Studies Of Cropland Soilsmentioning
confidence: 99%
See 1 more Smart Citation
“…The plot had recently been used to produce a cycle of cassava crop after land preparation in 2013. This one cycle of cassava production could have generated legacy effects originating from the fertilizer residues (particularly with immobile elements) (Liu et al, 2015;Sharpley et al, 2013). In view of this, soil testing was carried out prior to establishing the field trial to ensure these effects were taken into consideration.…”
Section: Methodsmentioning
confidence: 99%